Ecology‐inspired resilient and affordable system of systems using degree of system order. Issue 1 (17th August 2021) - Chatterjee, Abheek; Malak, Richard; Layton, Astrid
Abstract: An optimal trade‐off between resilience (the ability to survive and recover from disruptions) and affordability is highly desirable in System of Systems (SoS) architectures. However, it is difficult to design SoS architectures for these goals as existing resilience evaluation methods require detailed disruption models that are not readily available in the early stages of design. Biological ecosystems (nature's resilient SoS) achieve these goals through a unique balance of efficient and redundant interactions in their architectures—measured using the metric Degree of System Order (DoSO). This research tests if this ecological architecting principle and the DoSO metric are useful for designing resilient and affordable SoS. The resilience versus affordability tradespace of a large number of notional SoS architectures is investigated using the DoSO metric. Results indicate that the majority of Pareto optimal SoS architectures, under various disruptions, lie in the ecologically‐identified favorable DoSO range. Further, SoS architectures within this DoSO range were found to have better resilience and affordability attributes, in general, than the architectures outside it. DoSO evaluation does not require knowledge of disruption scenarios and is the first network architecture metric to consider resilience versus affordability trade‐offs, making it a valuable addition to the SoS engineering toolset.